2012
DOI: 10.1177/1466138111435447
|View full text |Cite
|
Sign up to set email alerts
|

Prisoners and their victims: Techniques of neutralization, techniques of the self

Abstract: Denial of the victim' is one of the five classic techniques described by Sykes and Matza in their seminal work on techniques of neutralization. Based on ethnographic field work in a Norwegian remand prison, this article explores this particular technique as it is employed by prisoners in their narratives about how they came to be imprisoned. I will argue that this particular technique of neutralization, understood by Sykes and Matza as part of the etiology of crime, might fruitfully be re-conceptualized as a F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 32 publications
1
47
0
5
Order By: Relevance
“…Previous research has shown that despite the explicit power imbalance in detention homes and other forced-treatment (or incarceration) institutions, such as prisons, inmates do not simply submit to the power being imposed on them, but engage in more or less dramatic forms of resistance (see, for example, Bengtsson, 2012;Bosworth & Carrabine, 2001;Cesaroni & Alvi, 2010;Fox, 1999;Ugelvik, 2012). This dissertation confirms these previous findings, but contributes by specifically illuminating resistance through particular subject positionings.…”
Section: Resisting Resident Subjectivitiessupporting
confidence: 76%
See 3 more Smart Citations
“…Previous research has shown that despite the explicit power imbalance in detention homes and other forced-treatment (or incarceration) institutions, such as prisons, inmates do not simply submit to the power being imposed on them, but engage in more or less dramatic forms of resistance (see, for example, Bengtsson, 2012;Bosworth & Carrabine, 2001;Cesaroni & Alvi, 2010;Fox, 1999;Ugelvik, 2012). This dissertation confirms these previous findings, but contributes by specifically illuminating resistance through particular subject positionings.…”
Section: Resisting Resident Subjectivitiessupporting
confidence: 76%
“…For example, by engaging in rhetorical struggles about what a criminal is with CBT program facilitators and thereby resisting self-examination and change (Fox, 1999). Another example is resistance by engaging in practices that contribute to a more positive identity construction, for instance, by using neutralizations 2 when constructing narratives about their crimes (Ugelvik, 2012). These studies illuminate that subjectivities cannot be completely determined institutionally.…”
Section: Treatment Methods and Subject Positioningmentioning
confidence: 99%
See 2 more Smart Citations
“…This often conflicts with the expectation that they enact remorse in a self-denunciatory manner. As Maruna (2001) and Ugelvik (2012) have pointed out, prisoners' denial and disagreement with the official narrative may indeed be an essential part of the formation of the redemptive narrative most consistent with desistance.…”
Section: Constructed Self-narratives In Prisonmentioning
confidence: 99%